New income streams for news agencies: the organization of information events - Núñez Fernández, Víctor; Martínez Vallvey, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
News agencies, like other media, have been affected by economic changes, digitalization and globalization, which have altered their main source of income, i.e. subscription’ fees. Private news agencies must seek new revenue streams or monetize journalistic activities that reinforce their professional work and brand image. In this work, we study how the Spanish agency Europa Press manages online events as a new way to obtain economic income, always managing content with a high journalistic component.